The implication of Richard Nixon did not remove the principle of currency value based on nation gold reserve. - Kayadibi, Saim; Mohamad Faudzi, Mohd Hasbullah (IIUM Press, 2011)
When we did our research on this topic, we found that the discussion of pegging of gold becomes broad and broader. In fact, the financial crisis that is happening now, some of the problem that could not be settled is the issue of currencies which the value is fluctuated. That is when we started to think whether the pegging back the currencies to the gold will reduce the problem ofthis financial crisis.